2014
DOI: 10.1021/pr400923g
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Virulence Factors in Leishmania infantum Strains by a Proteomic Approach

Abstract: Knowledge of Leishmania virulence is essential for understanding how the contact between the pathogen and host cells can lead to pathogenesis. Virulence in two L. infantum strains was characterized using macrophages and hamsters. Next, we used difference gel electrophoresis (DIGE) and mass spectrometry to identify the differentially expressed proteins. A total of 63 spots were identified corresponding to 36 proteins; 20 were up-regulated, in which 16 had been previously associated with Leishmania virulence. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
2
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 55 publications
2
29
2
2
Order By: Relevance
“…This number covered 10.1% of the~8000 open reading frames predicted for the Leishmania genome sequence, although post-translational modification and processing will significantly reduce this estimate. The total number of spots is slightly lower than that found in other studies of DIGE analysis on Leishmania infantum [25,26] and much lower than that found by Daneshvar et al [21]. Indeed, the total number of spots visualized in the DIGE can be influenced by several factors such as sample type (species/strains of parasite), sample preparation, size and the pH range of IPG strip, size of the gel, and also the detection parameters used.…”
Section: Discussioncontrasting
confidence: 54%
“…This number covered 10.1% of the~8000 open reading frames predicted for the Leishmania genome sequence, although post-translational modification and processing will significantly reduce this estimate. The total number of spots is slightly lower than that found in other studies of DIGE analysis on Leishmania infantum [25,26] and much lower than that found by Daneshvar et al [21]. Indeed, the total number of spots visualized in the DIGE can be influenced by several factors such as sample type (species/strains of parasite), sample preparation, size and the pH range of IPG strip, size of the gel, and also the detection parameters used.…”
Section: Discussioncontrasting
confidence: 54%
“…infantum ELISA; LC–MS/MS Post infection vs pre infection 19 12 2019 [ 48 ] 12 L . infantum ELISA; RP‐ LC‐MS/MS After infection 168 days vs before infection, 211 days after infection vs before infection and 211 days after infection vs 168 days after infection 15 15 2020 [ 47 ] 13 Proteins of Leishmania Between infective strain L. infantum 2DE; MALDI-TOF/TOF MS Abundance volume ratio in BH 400 strain of L. infantum vs BH 46 strain 32 31 2014 [ 50 ] 14 L. amazonensis IEF; 2DE; ESI-TOF MS/MS; Western blot Day 0 vs day 150 19 37 2014 [ 51 ] 15 L. donovani SDS-PAGE; Nano HPLC–MS/MS; Western blot VL vs CL 29 109 2015 [ 53 ] 16 L. tropica 2DE-MALDI-TOF/TOF MS Percent volume of spot in gel of VL vs CL 10 35 2015 [ 54 ] 17 <...>…”
Section: Differentially Modulated Proteins In the Host After mentioning
confidence: 99%
“…Da Fonseca Pires et al [ 50 ] compared two strains of L. infantum BH400 ( Canis lupus ) and BH46 (human) proteome to observe the virulence factor among the two strains. The study reported 32 and 31 proteins to be up-regulated and down-regulated, respectively, in the BH400 strain.…”
Section: Differentially Modulated Proteins Between Different Strains mentioning
confidence: 99%
“…A similar study compared proteomes of L. infantum chagasi promastigotes from strains with different virulence. The more virulent strain had higher levels of kinetoplastid membrane protein and metallopeptidase . Loss of virulence can also be achieved by axenic culture for many passages .…”
Section: Potential Applications Of Proteomics In Leishmaniasismentioning
confidence: 99%